Exertion-Induced Impairments in Cervical Spine Sensorimotor Control: Does Concussion History Matter? - Antonio Vintimilla; Roger James; Troy L. Hooper; Jean-Michel Brismée; Nathan Jarman; Vaishnavi Chiddarwar; Karthick Natesan; Aaron Likness; Lauren Adams; Brad Callan; Phil S. Sizer (Translational Journal of the American College of Sports Medicine, 2026)
Introduction: Cervical spine proprioception plays a role in head stabilization, postural orientation, and vestibular integration during sport. Even minor sensorimotor deficits can delay head reactions and increase injury risk, particularly under exertion. Subjects with a history of concussion may be even more vulnerable than healthy subjects. This study aimed to examine the effect of exertional fatigue on cervical joint position error (JPE) and sternocleidomastoid (SCM) muscle activity in males with and without a concussion history. Methods: Thirty-two males aged 18–50 years (16 ≥ 1 lifetime concussion, 16 controls) completed active cervical angle reproduction testing before and after a treadmill fatigue protocol. Absolute and constant JPE were recorded with bilateral SCM electromyography during angle relocation testing. A 2 (fatigue state) × 2 (group) mixed analysis of variance was used to compare outcomes. Alpha was set to 0.05, and ηp 2 was calculated for effect size (small = 0.01, medium = 0.06, large = 0.14). Results: Both groups recorded significant increases in absolute JPE ( P ≤ 0.001, ηp 2 = 0.55) and constant JPE ( P ≤ 0.001, ηp 2 = 0.48) postfatigue, exceeding reported minimal detectable change values. Overshooting became the predominant repositioning error after fatigue. Furthermore, there was a significant difference between groups for SCM amplitudes during JPE testing ( P = 0.02; ηp 2 = 0.16), where subjects with a history of concussion (≈72%–76% max) remained consistently elevated versus controls (≈40%–43% max). Conclusion: Exertional fatigue significantly worsened cervical proprioception in both groups. Neck muscle activity remained steady following fatigue but was consistently elevated in subjects with a concussion history. These findings suggest that subtle cervical sensorimotor deficits may be masked at rest but emerge under exertion. Furthermore, subjects with a history of concussion may require an increased allocation of neurocognitive resources for similar performance as their non-concussed counterparts. Incorporating fatigue-based cervical proprioception testing and targeted neck control training into sport conditioning or return-to-play evaluations may help identify at-risk athletes and reduce concussion vulnerability.